Influence of N2 flow rate on microstructure and properties of CrNx ceramic films prepared by MPP technique at low temperature. Issue 15 (1st August 2021) - Gui, Binhua; Zhou, Hui; Liu, Xingguang; Zhang, Kaifeng; Hu, Hanjun; Yang, Lamaocao; Zhang, Yanshuai
Abstract: In this study, CrNx ceramic films were prepared utilizing modulated pulsed power magnetron sputtering (MPP) technique at low deposition temperature, with varying flow rates of the reactive gas, i.e. N2 . The influences of N2 flow rate on the density of the plasma surrounding the target sheath, microstructure evolution, mechanical/tribological and anti-corrosion properties of the as-deposited CrNx ceramic films were investigated systematically. Results indicated that the plasma density increased sharply with increasing N2 flow rate in the range of 75 sccm to 175 sccm. Nevertheless, with further increase of N2 flow rate to 200 sccm, the growing trend of ionization slowed down probably due to the insufficiency of the power density. With increasing N2 flow rate, the Cr elemental concentration decreased from 69.7 at.% to 57.5 at.%, and that of N increased from 23.2 at.% to 36.6 at.%. The sub-stoichiometric ratio of the CrN films could be attributed to the relative lower reactive kinetic energy at low deposition temperature. The analyses on the microstructure evolution of CrNx films revealed that with insufficient introduced nitrogen, competitive growth between Cr2 N(110), Cr2 N(111), Cr(110) phases (note that all crystalline planes indexed here are parallel to the coating surface) were found; and with relative sufficient nitrogen, fcc-CrN phase took over, with preferred orientation of (111). Due to the improvement of density and the fine-grain strengthening mechanism, with 100 sccm N2 flow rate, the hardness of the CrNx films obtained the maximum value of 21.4 GPa. The films deposited at 75 sccm nitrogen showed the highest friction coefficient (i.e. ~0.75), which could be partially attributed to the presence of impurity particles on the film surface. And for the remaining films, the friction coefficient maintained in the range of 0.38–0.52. As for the anti-corrosion properties, the CrNx film deposited at 100 sccm nitrogen showed the lowest corrosion current (i.e. 44.2 nA/cm 2 ), indicating excellent anti-corrosion property.